KRITIK SASTRA PUITIKA KULTURAL STEPHEN GREENBLATT: METODE DAN PRAKTIK ANALISIS - Moh. Fathoni (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
As an exponent of new historicism, Greenblatt initiated cultural poetic in literary criticism . The broad and eclectic of Greenblatt‘s thought in various disciplines and also what he had adopted from other thinkers‘ theory strengthen in practising literary texts analysis, while Greenblatt ‘s writings about literary texts analysis were not formulated in the form of theories and praxis methods. In the other hand, it makes possible for anyone to formulate theories and methods for analysis according to literary criticism does. This paper describes a poetic culture literary critic of Stephen Greenblatt by trying to explore and understand the world through the analysis of his works. The formulation of Greenblatt‘s thought was proccesed by identifying some of his major books in the practice of literary text analysis, such as Renaissance Self - Fashioning: From More to Shakespeare (1980), Shakespearean Negotiations: The Circulation of Social Energy in Renaissance England (1988), and Marvelous possessions: The Wonder of the New World (1991).Keywords:new historicism, Greenblatt, poetic